THE EFFECT OF JAVANESE-LANGUAGE LEAFLET MEDIA TO INCREASE KNOWLEDGE AND ATTITUDES OF MOTHER AS CLEAN AND HEALTHY LIFESTYLE BEHAVIOR IN THE HOUSEHOLD ORDER ABOUT EXCLUSIVE BREAST MILK IN JOMBANG REGENCY - Siti Mudrikatin; Asef Wildan Munfadlila (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
ABSTRACT The role of health promotion media is very important in changing positive health behavior. Good health promotion media are those that see the level of community needs, while health promotion media in Jombang Regency are still centralized and not based on the needs of the local community. Regional language leaflets are expected to improve the knowledge and attitudes of mothers towards Clean and Healthy Life Behavior in the Household setting, especially on the exclusive ASI indicator. The purpose of this study was to analyze the influence of local language leaflet media on increasing knowledge and attitudes about Clean and Healthy Life Behavior of the household order exclusive breastfeeding in Jombang. This study uses quantitative methods, the type of research is queasy experimental with a non-equivalent control group design. This study also features qualitative techniques in the form of need assessment and pretesting for the development of leaflet media. Determination of the sample is done by purposive sampling technique, a sample of 60 thousand households consisting of 20 housewives in three districts in Jombang. The results showed that there were significant differences in knowledge (p value <0.001) and attitude (p value 0.001) between before and after treatment, where the increase in knowledge and attitudes in the treatment group using local language leaflets was higher compared to the treatment group with the media Indonesian language leaflets and groups without treatment (control). The suggestion in this study is that the use of regional languages Jawa language is not only on leaflet media, but also on other health promotion media in the form of print media. Keywords: Leaflet, Knowledge, Attitude, Clean and healthy life behavior of households, Exclusive ASI.